Enantioseparation and impurity determination of ambrisentan using cyclodextrin-modified micellar electrokinetic chromatography: Visualizing the design space within quality by design framework - Orlandini, S; Pasquini, B; Caprini, C; Del Bubba, M; Douša, M; Pinzauti, S; Furlanetto, S (Journal of chromatography. A, 2016)
A capillary electrophoresis method for the simultaneous determination of the enantiomeric purity and of impurities of the chiral drug ambrisentan has been developed following the Quality by Design principles. The selected separation system consisted of a micellar pseudostationary phase made by sodium dodecyl sulphate with the addition of γ-cyclodextrin. The effects of critical process parameters (capillary length, temperature, voltage, borate concentration, pH, sodium dodecyl sulphate concentration, γ-cyclodextrin concentration) on enantioresolution of ambrisentan and analysis time were extensively investigated by multivariate strategies involving a screening phase and Response Surface Methodology. The Design Space was defined with a desired probability level π≥90%, and the working conditions, with the limits of the Design Space, corresponded to the following: capillary length, 64.5cm; temperature, 22°C; voltage, 30kV (26-30kV); background electrolyte, 100mM borate buffer pH 9.20 (8.80-9.60), 100mM sodium dodecyl sulphate, 50mM (43-50mM) γ-cyclodextrin. A Plackett-Burman design was applied for robustness testing, and a method control strategy was established. The method was fully validated according to the International Conference on Harmonisation guidelines and was applied to ambrisentan coated tablets.
Keywords: Capillary electrophoresis; Pyridazines; Chiral separation; Hydrogen-Ion Concentration; Experimental design; dodecylsíran sodný; řízení kvality; Reproducibility of Results; Borates; cyklodextriny; boritany; Calibration; Buffers; Stereoisomerism; tablety; stereoizomerie; Chromatography, Micellar Electrokinetic Capillary; Impurities; chromatografie micelární elektrokinetická kapilární; pyridaziny; kalibrace; reprodukovatelnost výsledků; Quality Control; fenylpropionáty; Phenylpropionates; Ambrisentan; Drug Contamination; Quality by design; pufry; kontaminace léku; koncentrace vodíkových iontů; Tablets; Sodium Dodecyl Sulfate; Cyclodextrins